Beatrice Wines interviewed by Hazel de Berg in the Hazel de Berg collection - Wines, Beatrice; De Berg, Hazel, 1913-1984. (1963)
Wines speaks of her interest in books and about Fisher Library.
Also available online
Transcript available (2 p.)
Keywords: Wines, Beatrice -- Interviews; University of Sydney. -- Library; Women librarians -- Australia -- Interviews